Psychoactive tryptamines from basidiomycetes - Wurst, M; Kysilka, R; Flieger, M (Folia microbiologica, 2002)
The review lists natural sources, i.e. strains and species of fungi producing predominantly psychoactive tryptamines (indolealkylamines), their chemical structure and properties, toxic effects on the man and psychic symptoms of intoxication. It describes the biosynthesis and production of some tryptamines by the mycelial culture of Psilocybe bohemica Sebek, a survey of methods for their analysis and isolation. It evaluates the worldwide use and abuse of psychoactive fungi as sources of drugs in general and in the Czechia in particular during the last two and a half decades.
Keywords: psychotropní léky; tryptaminy; halucinogeny; dějiny 20. století; History, 16th Century; lidé; History, 17th Century; History, 20th Century; History, Ancient; Basidiomycota; dějiny 17. století; dějiny 16. století; Humans; Hallucinogens; Tryptamines; dějiny starověku; Psychotropic Drugs